El protocolo familiar. La contractualización en las familias empresarias para la gestión de las empresas familiares - Echaiz Moreno, Daniel (2010)
The family enterprises are a world phenomenon of great transcendency for the high number of them, nevertheless they meet overwhelmed by the problem of the generational transition that, in many occasions, it marks the beginning of the end of the family enterprise.